2008
DOI: 10.3989/gya.095307
|View full text |Cite
|
Sign up to set email alerts
|

Loss in tocopherols and oxidative stability during the frying of frozen cassava chips

Abstract: El objetivo de este trabajo fue analizar los cambios en la concentración de tocoferoles y la evolución de la alteración oxidativa en aceites vegetales utilizados en fritura discontinua. La fritura de palitos de mandioca congelados fue realizada en una freidora eléctrica doméstica, en la cual el aceite fue calentando a 180°C, durante 25 horas, con reposición de aceite fresco. Los resultados obtenidos de las determinaciones analíticas fueron sometidos a análisis de variancia, en esquema factorial para determinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…These researchers used rosemary extract to prevent oxidation, and they found that this antioxidant inhibited the increased formation of total polar compounds. Also, the increased formation of polar compounds after 25 h of heating was found when cotton and sunflower oils used to fry cassava were studied (Corsini et al 2009). The concentration of products that formed as a result of oxidative alteration of the oil increased as a function of temperature, limiting the usefulness of the oil.…”
Section: Total Polar Compounds and Oxidative Stabilitysupporting
confidence: 38%
See 1 more Smart Citation
“…These researchers used rosemary extract to prevent oxidation, and they found that this antioxidant inhibited the increased formation of total polar compounds. Also, the increased formation of polar compounds after 25 h of heating was found when cotton and sunflower oils used to fry cassava were studied (Corsini et al 2009). The concentration of products that formed as a result of oxidative alteration of the oil increased as a function of temperature, limiting the usefulness of the oil.…”
Section: Total Polar Compounds and Oxidative Stabilitysupporting
confidence: 38%
“…These researchers used rosemary extract to prevent oxidation, and they found that this antioxidant inhibited the increased formation of total polar compounds. Also, the increased formation of polar compounds after 25 h of heating was found when cotton and sunflower oils used to fry cassava were studied (Corsini et al . 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The stability of naturally occurring tocopherols in foods may be influenced by factors such as the fatty‐acid profile (Corsini, Silva, & Jorge, ) and storage conditions (Pignitter et al, ). In the present study, alpha‐ and gamma‐tocopherol were detected and their depletion over time was monitored (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of unsaturation has been shown to influence the oxidative stability of fats and oils but may also affect the stability of tocopherols. According to Corsini et al [27], the highest loss of total tocopherols was noted in sunflower oil (52%) as compared with palm oil (8%) after deep frying of frozen cassava chips, which was attributed to the lowest degree of unsaturation of the latter. Additionally, alpha-tocopherol was the most sensitive and delta-tocopherol the least sensitive in sunflower oil.…”
Section: Stability and Bioavailability Of Tocopherol And Tocotrienolsmentioning
confidence: 99%
“…In another study [102], alpha-tocopherol was also found to be the most sensitive to the blanching process conducted by the peanut industry. The above-mentioned studies [5,27,102] identified and quantified all four forms of tocopherol in their starting material, which is useful for comparative purposes. Tree nuts are also important sources of tocopherols [103]; gamma-irradiation decreased the content of alpha-tocopherol in walnuts by up to 87.4% when subjected to a dose of 8 kGy, and its concentration was under the detection limit in samples submitted to 10 kGy [104].…”
Section: Stability and Bioavailability Of Tocopherol And Tocotrienolsmentioning
confidence: 99%